Bulk vs. Surface Structure of 3d Metal Impurities in Topological Insulator Bi2Te3 - B. Leedahl (Nature Portfolio, 2017)
Abstract Topological insulators have become one of the most prominent research topics in materials science in recent years. Specifically, Bi2Te3 is one of the most promising for technological applications due to its conductive surface states and insulating bulk properties. Herein, we contrast the bulk and surface structural environments of dopant ions Cr, Mn, Fe, Co, Ni, and Cu in Bi2Te3 thin films in order to further elucidate this compound. Our measurements show the preferred oxidation state and surrounding crystal environment of each 3d-metal atomic species, and how they are incorporated into Bi2Te3. We show that in each case there is a unique interplay between structural environments, and that it is highly dependant on the dopant atom. Mn impurities in Bi2Te3 purely substitute into Bi sites in a 2+ oxidation state. Cr atoms seem only to reside on the surface and are effectively not able to be absorbed into the bulk. Whereas for Co and Ni, an array of substitutional, interstitial, and metallic configurations occur. Considering the relatively heavy Cu atoms, metallic clusters are highly favourable. The situation with Fe is even more complex, displaying a mix of oxidation states that differ greatly between the surface and bulk environments.